African tick-borne viruses: A systematic review of diversity, epidemiology, clinical impact, and one health strategies - Tsireledzo Goodwill Makwarela; Nimmi Seoraj-Pillai; Tshifhiwa Constance Nangammbi (Veterinary Research Communications, 2026)
Abstract Background Tick-borne viruses (TBVs) are emerging pathogens that affect human and animal health, yet their diversity, epidemiology, and clinical impact in Africa remain poorly synthesised. This systematic review aimed to map TBV diversity, quantify prevalence and seroprevalence, assess clinical outcomes, and evaluate the extent of One Health implementation in surveillance studies across Africa. Methods We searched PubMed, Embase, Scopus, Web of Science, CAB Abstracts, African Index Medicus, and grey literature up to 9 April 2026. Independent reviewers screened records, extracted data, and assessed risk of bias using the Joanna Briggs Institute tool for cross-sectional studies. The certainty of evidence was evaluated using GRADE. Heterogeneity was quantified using I², Cochran’s Q, and τ². Results Forty-six studies (45 cross-sectional, 1 method development) from 35 African countries were included. Crimean-Congo haemorrhagic fever virus (CCHFV) was the most frequently reported virus (22 studies), followed by African swine fever virus (ASFV, 5 studies) and tick-borne encephalitis virus (TBEV, 3 studies). Novel viruses (Kinna, Bogoria, Perkerra, Ntepes, Shibuyunji, Zaloxo) were also identified. Tick homogenate was the predominant sample type (62.9%). CCHFV minimum infection rates in ticks ranged from 0.13% to 11.3%, while livestock seroprevalence reached up to 98.2% (cattle) and 89.4% (camels). Human CCHFV seroprevalence in at-risk groups ranged from 1.9% to 11.8%, and Kinna virus showed a 38.6% seroprevalence among pastoralists. Only three studies (6.5%) explicitly adopted a One Health framework. Risk of bias was high in 71.7% of studies. Heterogeneity was considerable for CCHFV (I² = 99.9%), ASFV (I² = 99.4%), and JMTV (I² = 97.2%). GRADE certainty was very low for most viruses due to serious bias, inconsistency, indirectness, and imprecision. Conclusions CCHFV appears to be widely distributed across Africa based on available evidence, although the certainty of this evidence is very low, particularly given high livestock exposure. The overall evidence is of very low to low certainty. However, 71.7% of studies were at high risk of bias, and GRADE certainty was very low for most viruses, indicating that findings should be interpreted as hypothesis-generating rather than definitive. Novel tick-associated viruses are increasingly detected, yet integrated One Health surveillance remains rare. Future studies should adopt probability-based sampling, confirmatory diagnostics, and multi-sectoral approaches to improve the quality of evidence and inform control strategies.